Ontogenetical regularities of the organization of lymphoidformations of the human vermiform appendix in the late prenatal period of ontogenesis - Таврог, Маріанна Львівна; Сирцов, Вадим Кирилович; Зідрашко, Галина Анатоліївна (Запорізький державний медичний університет, 2018)
Purpose: to study the age features of lymphoid formations of human appendix in the late prenatal and early postnatal periods of ontogenesis. Materials and methods: 20 appendices of fetuses, newborns and infants who died from causes not related to diseases of the immune system and digestive organs. The age was determined by the autopsy protocols. The areas of the appendix were fixed in 10% formalin, poured into paraffin and stained with Carats haematoxylin and eosin. Reticular fibers were produced by impregnation with silver by Gomori. The cell composition was counted using the morphometric grid of A.A. Glagolev (1941) in the modification of S.B. Stefanova (1981, 1985), and statistical analysis - using tables RB. Strelkova (1980).
Keywords: тези